A reevaluation of the use of rhizome scars to age plants of Trillium erectum (Melanthiaceae)1. Issue 6 (1st June 2013) - Broyles, Steven B.; Smith, Sarah M.; Smith, Tori R.; Kindt, Justin R.
Abstract : Premise of study: Herbaceous perennials are important long‐lived plants in North American forests. Trillium has been used as a model organism to examine the effects of ecological processes on age structure in herbaceous forest perennials. Here, the methods of aging Trillium rhizomes are critically examined. Methods: Rhizomes of seedlings, single‐bract plants, three‐bract nonflowering plants, and flowering plants of Trillium erectum were examined. The patterns of cataphyll and scape scars on rhizomes were examined with respect to demographic category. Key results: Trillium rhizomes produce two cataphyll scars per year on single‐bract, three‐bract nonflowering, and flowering plants. Scape scars were only evident on rhizomes of three‐leaved nonflowering and flowering plants. The percentage of intact rhizomes ranged from 10–67% for three‐bract nonflowering plants, and 0–51% for flowering plants. Rhizomes in all demographic categories had evidence of recessing tissues from the oldest portion of the rhizome indicating that accurate age estimates are not possible on many plants. Conclusions: Accepted methods of aging Trillium rhizomes have significant drawbacks. The primary problem is that rhizomes rot from the oldest portions in all demographic categories. A second problem is that plants producing multiple scape scars in a given year could mistakenly be counted as multiple years. Finally, confusing terminology and misrepresentations in Trillium literature suggests that many previous studies did not correctly determine age. Given the challenges of aging Trillium, we suggest that future studies use rhizome aging to study early demographic stages only and the ecological processes that influence their growth.